THE CORRELATION BETWEEN STUDENTS’ LEARNING INTEREST AND THEIR ENGLISH ACHIEVEMENT AT SMAN 10 KENDARI - Yuliana, Yuliana; Sale, Firdaus; Nggawu, La Ode (Journal of Teaching of English, 2019)
The  purpose  of the research is to  find  out a  significant correlation between students'  learning  interest  and  their English achievement in SMAN 10 Kendari. The method used in conducting this research is correlation study. The results of the research show that there is significant correlation between students’ learning interest and their English achievement. It can be seen by the results of analysis using Correlation Product Moment with help program SPSS Version 16, it showed a significance value rxy is 0.382; df is 100 if it is compared with the r table at the degree of significance 5% (0.195) and 1% (0.254), the correlation between students’ learning interest and their English achievement is significant (rxy: rtable= 0.382 > 0.195; rxy: rtable  = 0.382 > 0.254) it means that H0  rejected and H1 accepted. Thus it can be concluded that there was significant correlation between students’ learning interest and  their  English  achievement at SMAN 10 Kendari in academic year 2016/2017. Keywords: Correlation, Learning Interest, English Achievement